CRIMINAL LIABILITY OF ROAD ORGANIZERS IN THE PERSPECTIVE OF LAW NUMBER 22 YEAR 2009 CONCERNING TRAFFIC AND ROAD TRANSPORTATION - Andi Najemi; Kabib Nawawi (Berumpun: International Journal of Social, Politics, and Humanities, 2020)
The specific goal of this research is to know and analyze the provisions of norms or legal norms relating to the criminal liability of road organizers from the dogmatic aspects of the law and legal principles. Since there is a norm vacuum of Law Number 22 Year 2009 concerning Traffic and Road Transportation, if the road organizer does not exercise its authority, it will result in a criminal offense then this law cannot be implemented or impaired. The statement of the problem in this research is how criminal liability of the Road Organizers and Road Transportation according to Law Number 22 Year 2009 concerning Traffic and Road Transportation. This research is normative. The data were obtained by a detailed analysis of legal materials, primary, secondary and tertiary law. The specification of this research is the pure legal research to get a picture of one problem, namely about the criminal responsibility of the road organizer from the perspective of Law Number 22 Year 2009, concerning Traffic and Road Transportation. Through the legislative approach (normative approach), which is the approach to the applicable laws and regulations to obtain a basis for discussing issues related to traffic and road transport crimes, including legislation Law Number 22 Year 2009, concerning Road Traffic and Transport Law Number 38 of 2004, Concerning Roads, Government Regulation Number 43 of 1993 concerning Road Infrastructure and Traffic. The results of the study indicate that there is a blurring of norms in Law Number 22 Year 2009, especially regarding the concept of road organizers as regulated in Article 24 and Article 273. as a result, the article cannot be operational. So that criminal liability for road organizers if they make a mistake on the formulas of article 24 and article 273 is difficult to account for. Although the organizer of the road as a legal subject if making a mistake should be responsible and can be held responsible based on the theory of strict liability and vicarious liability. The conclusion is that Law No. 22/2009 concerning Road Traffic and Transport does not regulate the concept of road organizers so that if a road organizer makes a mistake as regulated in Article 24 and Article 273 it is difficult to be accounted for, thus ensuring that there is a blurring of norms in The law and unworking.